Malay Women in Syair Putri Akal: A Ricoeur’s Hermeneutic Study - Syafira Anna Dzirin; Wachid Eko Purwanto; Yosi Wulandari (Universitas Muhammadiyah Malang, 2025)
This study examines the representation of Malay women in Syair Putri Akal using Paul Ricoeur's hermeneutic approach to strengthen the cultural identity of women that are often marginalized in historical narratives and classical literature. The background of this study is based on the importance of representing portraits of women in classical literary texts to understand the cultural roles they once held. This study aims to examine the representation of Malay women from their physical, character, and psychological images through an interpretive approach. The method used is qualitative with Paul Ricoeur's hermeneutic theory, which includes the stages of distanciation, interpretation, and appropriation, to explore the poem's symbolic meaning. The results show that the character of Putri Akal is represented as a physically beautiful woman, has intelligence and wisdom in character, and is ethereal and gentle psychologically. The symbolization of beauty and reason in the character of Malay women shows the idealism of Malay culture towards women. In conclusion, Syair Putri Akal places women as objects and as active subjects in social and cultural processes. Hence, building a more equal narrative of women's identity is relevant.